Comparing two-digit numbers: The importance of being presented together. - Ganor-Stern, Dana; Pinhas, Michal; Tzeglov, Joseph (Quarterly Journal of Experimental Psychology, 2009)
A study examined the impact of presentation mode on magnitude comparisons of two-digit numbers using the stimuli set developed in 2001 by Nuerk, Weger, and Willmes. In Experiment 1, only number pairs from difference decades were either simultaneously or sequentially introduced. Simultaneous presentation showed the parallel processing of both the units and decades digits and for a components representation. Sequential presentation revealed the processing of mainly the decades digits. In Experiment 2, within-decade number pairs were included to make both the units and decades digits task relevant. Findings from the simultaneous condition demonstrated consistency with a components representation, whereas those from the sequential presentation were more aligned with a holistic representation in keeping with Zhang and Wang's research.